Parasite Genomics Protocols - Melville, Sara E.; Melville, Sara E. (Methods in Molecular Biology,, 2004)
Parasitic disease remains an important health issue in most regions of the world and constitutes a major cause of morbidity and mortality in developing countries. In Parasite Genomics Protocols, pioneering bench researchers describe in detail the cutting-edge techniques they have developed for analyzing the genomes and gene products in a diverse range of protozoan and metazoan parasites. These readily reproducible techniques can be used in genomic, functional genomic, and postgenomic studies and include transfection methods and vectors for several protozoan parasites, global analysis using microarrays, gene ablation using RNA interference, gene knockout, mutagenesis, and chromosome manipulation. Some of the protocols require DNA sequence data, whereas others were developed independently of whole-genome sequence data. Additional chapters survey the available genome sequences, helping novice researchers overcome the difficulties of accessing the databases and applying bioinformatics analysis to biological function. The protocols presented follow the successful Methods in Molecular Biology™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of equipment and reagents, and tips on troubleshooting and the avoidance of known pitfalls. State-of-the-art and highly practical, Parasite Genomics Protocols offers bench investigators in parasitology a wide-ranging collection of diverse methods for elucidating the content of the genomes of parasitic organisms, utilizing the genome sequence for genetic analysis, and ascribing function to the available genome sequences.